Polemik Pengesahan Omnibus Law: UU Cipta Kerja Dalam Perspektif Sosiologi Hukum - Karinina Anggita Farrisqi; Agus Machfud Fauzi (UIR Press, 2021)
A law with a concept on the omnibus law in the world of law in the State of Indonesia is a new perspective in the field of law. The point in omnibus law is different from the meaning, nature, and concept of legal norms in existing laws. We can also interpret this concept as a way of settling the forms of regulation in legislation into law and which in the end have consequences for revoking some invalid regulations. With the use of a new perspective like this, of course, people's thinking is also increasingly modern, including following the flow of globalization. In this era of globalization, there are certainly many incidents in the spread of hoax news. This problem is carried out by qualitative research methods and using several theories. The subject matter to be discussed can also be found in the conclusion that the perspective used by the drafters of the law is increasingly modern which will also provide the potential for the spread of hoaxes from people who follow the flow of globalization. Therefore, if the government and the DPR enforce themselves in making laws with the concept of the omnibus law, then the formation process needs to follow the method of prolegnas, has a good academic script, and is not in a hurry by involving stakeholders and the community.